Social Media User X's Sentiment Towards Omnibus Health Law in Indonesia - Prastowo, Muhammad Yogie; Lazuardi, Lutfan; Kristina, Susi Ari (Indonesian Journal of Global Health Research, 2024)
The Health Omnibus Law aims to reform the health sector. Prior to its enactment, public responses emerged in various forms, one of which was by expressing opinions on X social media. Objective: This study aims to determine public sentiment towards the Omnibus Health Law and its behaviour based on speech act theory. Method: Qualitative data was obtained retrospectively by means of text mining or extracting tweets using the hashtags #UUKesehatanOmnibuslaw and #UUKesehatan. From a total of 1,960 sent from 11 July to 31 August 2023, descriptive research was carried out with a qualitative approach on these tweets. Then classify sentiment using the Naïve Bayes algorithm and classify using speech act theory analysis. Results: 1,960 tweets were found that met the criteria. The results showed that neutral sentiment (94.13%) dominated the tweets compared to negative sentiment (3.16%) and positive sentiment (2.70%). There were 9 themes found in the tweets, with the dominant theme being ‘laws and government’. Conclusions: The results showed that the majority of tweet users were assertive and gave 'statements’ in response to the omnibus health law